The Church of Ireland in Belfast: 1800-1870 - Kerr, Stephen Peter (The University of Edinburgh, 1979)
This thesis is an account of the life of the Established Church of Ireland in Belfast during the first seventy years of the 19th century. It may seem an uneven account, with more attention being paid to the final forty years of the period than to the first thirty. This inbalance is due to their being less material dealing with the early period available, perhaps because Belfast, and consequently the Church in the city, did not begin to expand until the late 1820's.

Chapter I - "Belfast 1800-1870" - describes the development of Belfast during the period, so that the Church might be seen in its poli¬ tical, social and economic context. It traces the city's growth from being a small town in the early 1800's to a large industrial city by 1870, indicating some of the problems attendanton such a transformation. The growth of hostility between the Catholic and Protestant communities is noted

Chapters II, III, IV and V deal with different aspects of the Church's response to the changing situation of Belfast. In "The Church Becalmed" (II), the Church in Belfast is considered against the background of the Established Church in Ireland at the turn of the 19th century. The conclusion is offered that until the mid l820's, the Church in Belfast very much shared the characteristics of the Established Church in the the. rest of the country - of calmness, staidness and slight superiority.

"The Church Concerned" (III) relates the Church's growing awareness of the growth of Belfast and her response to it in terms of Church extension. The involvement of the Church with the rising population of the city is considered in Chapter IV, while "The Church Militant" (V) examines the emergence of a narrow and aggressive evangelical protestantism in the life of the Church.

I conclude:

(1) that the Church of Ireland in Belfast after 1830 was remarkably energetic and stridently confident in her outreach to the growing city, although not very successful.

(2) that the Church became increasingly anti-Catholic as the century progressed.

3) that after 1850 the laity began to play an important role in the mission and organisation of the Church.